Valuation ash bagasse Nicaraguan sugar industry as part Portland cement substitute (Nexo Revista Científica, 2014)
In this study, the use of the ashes of sugarcane bagasse (ASB) from Monte Rosa sugarcane mill (Nicaragua) as an alternative material to Portland Cement (PC) was evaluated. The evaluation was performed through studies of advanced characterization and mechanical properties in pastes with 15% and 45% substitution of PC. Moreover, 100% PC pastes were used as reference. The mechanical resistance (MR), the consumption of calcium hydroxide and the development of reaction products were measured. The results showed that the highest values of MR were obtained for the reference pastes, thus indicating that the MR decreased with increase in the degree of substitution. Through the analysis of X-ray diffraction (XRD) and thermal analysis TGA / DTA was found that the consumption of Ca(OH)2 gave rise to the formation of CSH gel as the main product of hydration and caused the gain in the mechanical properties. The reaction products were observed by scanning electron microscopy (SEM) where the mechanism in solid state was noticeable. From this result, it can be concluded that the ASB are pozzolanic material with a better reactivity to Ca(OH)2 with 15% of substitution. DOI: http://dx.doi.org/10.5377/nexo.v27i2.1944